Sosialisasi Strategi Pengembangan Ekowisata Pantai Lampu Satu Sebagai Upaya Meningkatkan Pendapatan Masyarakat Lokal - Ismail; Parman; Ratu Bulkis Ramli; Sri Hanipah; Ilham Majid (Yayasan Perguruan Kampus, 2023)
This community service was carried out based on observations related to the tourist destination of Lampu Satu Beach in Merauke Regency. The fundamental problems found are; a) the low understanding of local people regarding tourist attractions as economic support; b) public understanding related to the management of tourist attractions in supporting tourism development is still very limited; c) there are still unclear regulations in the management of Lampu Satu beach as a tourist attraction. The method used in this service is the lecture and discussion method. Based on the results of the problem analysis, several programs can be formulated several programs, namely; socialization related to the Ecotourism Development Strategy of Lampu Satu Beach and the Eco-creative Development Strategy of Local Communities in the tourist attractions of Lampu Satu Beach. The achievement of community service activities at Lampu Satu beach can be seen quantitatively. Several ecotourism development strategies have been implemented, although their application is still not optimal. In this case, the role of the government, local communities, and managers of tourist attractions is very influential in the development of Lampu Satu Beach ecotourism as an effort to increase the income of local communities.